The Effect of Nanoceria on the Probiotic Properties of Bacillus amyloliquefaciens ssp. plantarum Strains - Safronova, L.A.; Roy, A.O.; Skorochod, I.O.; Pylypiuk, Y.V.; Сафронова, Л.А.; Рой, А.О.; Скороход, І.О.; Пилипюк, Є.В. (PH "Akademperiodyka" of the NAS of Ukraine, 2024)
A novel approach to the therapeutic enhancement of probiotics is their integration with distinctive (having a positive effect on living organisms) nanoparticles. The aim of the study was to examine the impact of nanoceria (nano-CeO2) on the growth of probiotic bacilli, as well as on their antimicrobial activity and antioxidant potential, with the intention of developing a biocomposite preparation for the prevention and treatment of infections. Methods. The number of viable bacterial cells was determined by the tenfold dilution method. The antimicrobial activity of probiotics was evaluated by disk diffusion, well diffusion tests, and measurement of growth inhibition zones of test cultures (Proteus vulgaris, Escherichia coli, Staphylococcus aureus, Candida albicans, Pseudomonas aeruginosa). The antioxidant potential of cell-free supernatants of probiotic bacteria was studied using spectrophotometric methods. Results. The growth activity of probiotic strains Bacillus amyloliquefaciens ssp. plantarum IMV B-7142 and Bacillus amyloliquefaciens ssp. plantarum IMV B-7143 reached its maximum when grown with 0.01 mM nano-CeO2. This concentration was determined to be optimal. When testing the antimicrobial activity of probiotic bacilli under the influence of nano-CeO2, its stimulating effect was revealed, but to a different degree for each of the two studied strains. B. amyloliquefaciens ssp. plantarum IMV B-7142 inhibited the growth of opportunistic pathogenic test cultures more actively than strain IMV B-7143. The antioxidant potential of cell-free supernatants of the studied bacteria was enhanced by nano-CeO2, although to varying degrees. In particular, the activity of hydroxyl radical scavenging  markedly increased compared to the control. Conclusions. Consequently, nano-CeO2, due to its stimulatory effect on the physiological and biochemical activity of B. amyloliquefaciens ssp. plantarum IMV B-7142 and IMV B-7143, may be a promising component of a biocomposite preparation.